Identification and functional characterization of nuclear receptors with roles in the reproductive development and approaches to establish genome editing in Schistosoma mansoni - Möscheid, Max Frederik; Justus Liebig University Giessen (My University, 2024)
Schistosoma mansoni is a parasite of humans and animals and causes the infectious disease schistosomiasis. Schistosomes are the only trematodes to have evolved separate sexes. Furthermore, females reach sexual maturity only if they are permanently paired with a male. Previous comparative transcriptomics studies of adult schistosomes and their isolated gonads have revealed that genes encoding type II nuclear receptors (NRs) are regulated in a pairing dependent and tissue-specific manner with a preference for the female ovary. Members of the nuclear receptor superfamily are ligand-activated transcription factors that play diverse roles in cell differentiation, development, and proliferation. In vertebrate systems, type II NRs, such as retinoic acid receptors (RAR/RXR) and thyroid hormone receptors (THR) have been reported to be involved in spermatogenesis, embryogenesis, and tissue homeostasis. In the course of this work, potential S. mansoni NRs orthologs were identified and assigned to different NR classes as RAR (Smp_144170, SmRAR), RXR (Smp_097700, SmRXR-1), THRα (Smp_134490, SmTHRα), and THRβ (Smp_174260, SmTHRβ) based on polygenetic and comparative domain analyses. In addition, whole mount in situ hybridization (WISH) and functional analyses using RNA interference (RNAi) were performed to characterize these previously uncharacterized S. mansoni NR orthologs. Using WISH, transcripts of these receptors were found in the posterior part of the ovary. In addition, transcripts of these receptors dominated in oocytes at the intermediate stage of development, which was recently discovered by a new scRNA-Seq atlas of isolated ovaries of paired females, work performed by Zhigang Lu, a former member of the Grevelding lab. In my work, functional analyses provided first evidence for the involvement of these receptors in early embryogenesis and tissue homeostasis in adult schistosomes. Morphological analyses following RNAi revealed changes in the cellular structure of the ovary of paired females. In particular, RNAi against SmRAR and SmRXR-1 as well as biologically associated molecules, such as SmMEIOB and SmGLI1, strongly suggested essential roles of these genes in oocyte maturation and meiotic progression. These results as well as subsequent analyses of the influence of 9cis-retinoic acid on egg production suggest a critical role for RA signaling in the reproductive biology of S. mansoni. The second aim of this project was to establish a CRISPR/Cas-based editing method for S. mansoni. Knock-out models are commonly used to study the function of a gene of interest (GOI). However, in the post-genomic era of schistosome research, there is no established protocol for stable transformation of this and other platyhelminth parasites. To date, RNAi has been the most appropriate method for functional gene characterization. Though, RNAi efficiency is variable and can lead to ectopic effects. CRISPR/Cas-based editing is a powerful tool for gene characterization. To make this technique accessible for trematode research, a protocol was established to edit a genomic safe harbor (GSH) site of S. mansoni, which was bioinformatically predicted before by our collaboration partner Professor Christoph Grunau (Perpignan) and named GSH1. GSHs represent distinct sites in the genome that tolerate the integration of new genetic material without compromising genome integrity or gene expression. Thus, GSHs should allow the constitutive expression of reporter-genes. In order to edit the identified candidate GSH1, a 5'C6-PEG10 modified construct encoding an eGFP-reporter gene under a strong native S. mansoni promoter was used as a donor repair template. Cas-mediated integration of the transgene was achieved by electroporation of eggs. To this end, Cas9 and Cas12a were used in a comparative approach. Sequence analyses post editing showed differences in the reporter gene-integration efficiencies between the two enzymes with a bias for Cas12a. Nonetheless, integration of the reporter-gene into GSH1 was demonstrated by PCR for both ribonucleoprotein complexes formed by Cas9 or Cas12a. Moreover, this work succeeded in transferring transgenic larvae into the parasitic life cycle. Finally, eGFP signals were detected in eggs and adult worms, which demonstrated reporter-gene activity at GSH1. In summary, strong evidence was found for SmRAR and SmRXR-1 as key factors in the regulation of meiosis in S. mansoni. In addition, SmTHRβ and SmRXR-1 were shown to be critical for tissue homeostasis and oocyte formation. These findings suggest that these receptors and their ligands play a vital role in schistosome reproduction and indicating that the sexual maturation of females is not only influenced by pairing, but also by the host environment and thus by host derived molecules (e.g. RA and TH). Furthermore, the successful editing of the schistosomal GSH1 by transgene knock-in and the expression of the integrated eGFP reporter gene was achieved. By analyzing transgenic worms, strong evidence was found for transgene integration into germline cells. For the first time in schistosome research, these results provided proof of concept for a new genome editing approach in S. mansoni. This opens new perspectives to fill one of the existing technical gaps in schistosome research.
Keywords: Pairing dependent gene regulation; Schistosoma mansoni; trematodes; molecular parasitology; nuclear receptors; retinoic acid receptor; oogenesis; transgenesis CRISPR/Cas12a; ddc:570